Association between breast-feeding practices and sucking habits: A cross-sectional study of children in their first year of life - Moimaz, Suzely Adas Saliba [UNESP]; Zina, Livia [UNESP]; Saliba, Nemre Adas [UNESP]; Saliba, Orlando [UNESP] (Wolters Kluwer, 2008)
In addition to providing nutrition and immunological protection, breast-feeding has positive effects on the development of the infant's oral cavity. The aim of the present study is to assess breast-feeding patterns and to analyze the influence of breast-feeding practices and maternal sociodemographic variables on the prevalence of non-nutritive sucking habits in a sample of Brazilian infants. This cross-sectional study was carried out in Southern Brazil. A random sample of 100 mothers of infants up to 12 months of age was interviewed during the National Vaccination Campaign Day. The prevalence and median duration of breast-feeding were assessed. Breast-feeding practice, the exposure factor, was categorized as exclusive breast-feeding, predominant breast-feeding, complementary breast-feeding, or weaning. Maternal sociodemographic variables included age, race, marital status, educational level, profession, and family income. The outcome investigated was the prevalence of sucking habits (pacifier use and thumb sucking). We used two-sample tests, the chi-square test and Fisher exact test0 for statistical analyses of the data. The study revealed that 75% of infants were being breast-fed. Pacifier use and thumb sucking were common in 55%. Bottle-feeding was prevalent in 74% of infants. Breast-feeding was negatively correlated with pacifier use and thumb sucking (OR = 0.11; 95% CI: 0.03 to 0.4). Bottle-feeding was strongly associated with weaning (p = 0.0003). Among the sociodemographic variables, only marital status showed a statistical association with sucking habits (p = 0.04). These findings suggest that breast-feeding can prevent the occurrence of sucking habits. Although we could not evaluate causality assessment, malocclusion prevention seems to be yet one more reason for promoting breast-feeding practices.
Keywords: Bottle-feeding; Breastfeeding; Finger sucking; Habits; Malocclusion; Pacifiers; Risk factors; adolescent; adult; age; bottle feeding; Brazil; breast feeding; comparative study; cross-sectional study; educational status; female; habit; human; income; infant; male; marriage; occupation; pacifier; physiology; poverty; race; risk factor; statistics; sucking; urban population; weaning; Adolescent; Adult; Age Factors; Bottle Feeding; Breast Feeding; Continental Population Groups; Cross-Sectional Studies; Educational Status; Female; Fingersucking; Humans; Income; Infant; Male; Marital Status; Occupations; Poverty; Risk Factors; Sucking Behavior; Urban Population; Weaning; Young Adult